Preparation and performance evaluation of Zn-N-TiO2 nanoparticles-containing dental adhesive - Rong Han; Zhimin Zhang; Yuanhang Zhao; Linlin Yan; Wenjun Tang; Hong Zhang (Polymer Testing)
Dentin adhesives (DAs) are essential for securely bonding restorations to tooth structures. Traditional DA formulations exhibit insufficient antibacterial properties, resulting in increased susceptibility to secondary caries at the adhesive interface, ultimately compromising restoration longevity. Thus, to improve the success rate of treatment, developing new antibacterial DAs is crucial. In this study, we synthesized zinc and nitrogen co-doped titanium dioxide (Zn-N-TiO2) with a predominantly anatase-phase structure, which exhibits antibacterial properties through the generation of reactive oxygen species (ROS). We selected nanoparticles with a 3 % doping concentration of Zn and N for their notable antibacterial activity, and then added them into DAs at varying mass ratios. Experimental results demonstrated that the DAs effectively inhibited Streptococcus mutans (S. mutans). With the exception of the 7 wt% group, the cytotoxicity levels in all other groups were 0 or I, indicating high biocompatibility. The tensile bond strength (TBS) ranged from 30.66 ± 3.22 MPa to 32.04 ± 2.24 MPa, which indicates its potential to provide reliable bonding performance in clinical applications. This research offers valuable insights for the development of antibacterial DAs.